Selenium and vitamin E together improve intestinal epithelial barrier function and alleviate oxidative stress in heat‐stressed pigs. Issue 7 (10th May 2016) - Liu, Fan; Cottrell, Jeremy J.; Furness, John B.; Rivera, Leni R.; Kelly, Fletcher W.; Wijesiriwardana, Udani; Pustovit, Ruslan V.; Fothergill, Linda J.; Bravo, David M.; Celi, Pietro; Leury, Brian J.; Gabler, Nicholas K.; et al.
New Findings: What is the central question of this study? Oxidative stress may play a role in compromising intestinal epithelial barrier integrity in pigs subjected to heat stress, but it is unknown whether an increase of dietary antioxidants (selenium and vitamin E) could alleviate gut leakiness in heat‐stressed pigs. What is the main finding and its importance? Levels of dietary selenium (1.0 p.p.m.) and vitamin E (200 IU kg −1 ) greater than those usually recommended for pigs reduced intestinal leakiness caused by heat stress. This finding suggests that oxidative stress plays a role in compromising intestinal epithelial barrier integrity in heat‐stressed pigs and also provides a nutritional strategy for mitigating these effects. Heat stress compromises the intestinal epithelial barrier integrity of mammals through mechanisms that may include oxidative stress. Our objective was to test whether dietary supplementation with antioxidants, selenium (Se) and vitamin E (VE), protects intestinal epithelial barrier integrity in heat‐stressed pigs. Female growing pigs ( n = 48) were randomly assigned to four diets containing from 0.2 p.p.m. Se and 17 IU kg −1 VE (control, National Research Council recommended) to 1.0 p.p.m. Se and 200 IU kg −1 VE for 14 days. Six pigs from each dietary treatment were then exposed to either thermoneutral (20°C) or heat‐stress conditions (35°C 09.00–17.00 h and 28°C overnight) for 2 days. Transepithelial electrical resistance and fluorescein isothiocyanate–dextran (4 kDa; FD4) permeability were measured in isolated jejunum and ileum using Ussing chambers. Rectal temperature, respiratory rate and intestinal HSP70 mRNA abundance increased (all P < 0.001), and respiratory alkalosis occurred, suggesting that pigs were heat stressed. Heat stress also increased FD4 permeability and decreased transepithelial electrical resistance (both P < 0.01). These changes were associated with changes indicative of oxidative stress, a decreased glutathione peroxidase (GPX) activity and an increased glutathione disulfide (GSSG)‐to‐glutathione (GSH) ratio (both P < 0.05). With increasing dosage of Se and VE, GPX‐2 mRNA ( P = 0.003) and GPX activity ( P = 0.049) increased linearly, the GSSG:GSH ratio decreased linearly ( P = 0.037), and the impacts of heat stress on intestinal barrier function were reduced ( P < 0.05 for both transepithelial electrical resistance and FD4 permeability). In conclusion, in pigs an increase of dietary Se and VE mitigated the impacts of heat stress on intestinal barrier integrity, associated with a reduction in oxidative stress. Abstract :